Seismic strengthening of improperly repaired reinforced concrete columns using CFRP confinement. (December 2020) - Elci, Hasan
Highlights: An experimental program was carried out on RC columns. The seismic behavior of repaired, strengthened and as-built columns were compared. Seismic performance of improperly repaired columns was dramatically decreased. Seismic properties of columns strengthened with CFRP were recovered except stiffness. Abstract: In this study, lack of strength, stiffness, energy dissipation and ductility characteristics of the improperly repaired RC square columns were examined and the recoverability of seismic performance with the external Carbon Fiber Reinforced Polymer (CFRP) confinement was investigated. A total of six RC columns were tested for three times with different test stages; as-built, improperly repaired with Normal Strength Concrete (NSC) and retrofitted with CFRP confinement. In the first tests, relatively high axial load (0.40Ac fc ) and cyclic lateral load up to 15% lateral strength loss were applied to expose heavy damage on test columns. After that, the damaged columns repaired by using NSC and retested under the same loading conditions. In the first two test stages, the drift ratio at the end of tests was approximately 5%. The lateral strength, stiffness, ductility and energy dissipation characteristics of the improperly repaired columns dramatically decreased. At the last stage tests, the stiffness of strengthened columns was considerably reduced due to the damage that occurred in the concrete core after the two pre-damage phases. The lateral strengths of the CFRP retrofitted columns did not change much compared to the as-built columns because of the quality of the repairing concrete (26 MPa and 54 MPa) and the strain hardening behavior of steel reinforcement. Compared to the as-built columns, the cumulative energy dissipation capacities of columns were significantly increased, however, ductility increase was not achieved for all specimens because of the dramatic loss of stiffness.